Конституційне законодавство України: сучасний стан та тенденції розвитку - Крусян, Анжелика Романовна; Крусян, Анжеліка Романівна; Krusyan, Аnjelika R. (My University, 2011)
The article describes the content and gives the notion of constitutional law. Based on the analysis of Ukrainian legislation and legislative activities of the Verkhovna Rada of Ukraine disadvantages of constitutional law at the present stage of its development are presented. With the goal of constitutional reforms in Ukraine the main trends of development of constitutional law are justified and revealed. In particular attention is paid to such trends as: intensification, innovation, adaptation to the legislation of the European Union, the socialization and humanization, democratization, and the tendency to increase the knowledge-intensity of the process of creating the constitutional law of Ukraine. Systematized and convincing list of draft laws is provided, necessary for the adoption of constitutional and legal provision of the current stage of reform and modernization in Ukraine. The author substantiates the importance and the need to systematize the constitutional law of Ukraine and outlines a model scheme of its incorporation.
Крусян А.Р. Конституційне законодавство України: сучасний стан та тенденції розвитку / А. Р. Крусян // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2011. – Т. 10. – С. 47-57.
Keywords: конституційне законодавство; тенденції розвитку конституційного законодавства; конституційна реформа і модернізація; систематизація конституційного законодавства; конституционное законодательство; тенденции развития конституционного законодательства; конституционная реформа и модернизация; систематизация конституционного законодательства; constitutional law; constitutional law trends; constitutional reform and modernization; the systematization of constitutional law